Electromagnetic Interference Shielding Effectiveness of Copper Foil Coated Oriented Strand Board - Kaya, Ali İhsan; Çifci, Ahmet (Burdur Mehmet Akif Ersoy Üniversitesi, 2018)
The influence of growth of electronics industry and its widespread use in communications, automation, biomedical, space and other fields leads to many electromagnetic interference problems. Electromagnetic interference is the deterioration of operation of an electronic device when it is in the close neighborhood of an electromagnetic field in the radio frequency spectrum that is caused by another electronic device. This deterioration affects electronic devices as well as human health. Therefore, there is a need to effectively protect against the adverse effects of electromagnetic interference. In this paper, copper board and oriented strand board were used as a hybrid composite material. The interface and surface of oriented strand board were coated with copper foil and the metal cage was formed. It was found that electromagnetic shielding effectiveness in the frequency range of 1.88 GHz - 2.62 GHz and 5.20 GHz - 5.62 GHz of the oriented copper foil coated oriented particle board was acceptable.

Elektronik endüstrisinin büyümesinin ve haberleşme, otomasyon, biyomedikal, uzay ve diğer alanlardaki yaygın kullanımının etkisi birçok elektromanyetik girişim sorununa yol açmaktadır. Elektromanyetik girişim bir elektronik cihazın, başka bir elektronik cihazdan kaynaklanan, radyo frekansı spektrumunda bir elektromanyetik alanın yakınında çalışmasıyla ortaya çıkan bozulmadır. Bu bozulma elektronik cihazları etkilediği gibi insan sağlığını da etkilemektedir. Bu nedenle, elektromanyetik girişimin olumsuz etkilerinden etkili bir şekilde korunma ihtiyacı ortaya çıkmaktadır. Bu makalede, yönlendirilmiş yonga levha ile bakır levha karma kompozit malzeme olarak kullanılmıştır. Yönlendirilmiş yonga levhanın ara yüzeyi ile yüzeyi bakır folyo ile kaplanarak metal kafes oluşturulmuştur. Bakır folyo kaplı yönlendirilmiş yonga levhanın 1.88 GHz ile 2.62 GHz ve 5.20 GHz ile 5.62 GHz frekansları arasında elektromanyetik soğurma etkinliğinin kabul edilebilir düzeyde olduğu görülmüştür.
Bakır Folyo Kaplı Yönlendirilmiş Yonga Levhanın Elektromanyetik Girişimi Soğurma Etkinliği
Keywords: Engineering; Mühendislik